Bioethanol production from agarophyte red seaweed, Gelidium elegans, using a novel sample preparation method for analysing bioethanol content by gas chromatography - Hessami, Mohammad Javad; Cheng, Sit Foon; Ambati, Ranga Rao; Yeong, Hui Yin; Phang, Siew Moi (Springer Verlag (Germany), 2019)
In this study, Gelidium elegans is investigated for ethanol production. A combination of factors including different temperatures, acid concentration and incubation time was evaluated to determine the suitable saccharification conditions. The combination of 2.5% (w/v) H2SO4 at 120 °C for 40 min was selected for hydrolysis of the seaweed biomass, followed by purification, and fermentation to yield ethanol. The galactose and glucose were dominant reducing sugars in the G. elegans hydrolysate and under optimum condition of dilute acid hydrolysis, 39.42% of reducing sugars was produced and fermentation resulted in ethanol concentration of 13.27 ± 0.47 g/L. A modified method was evaluated for sample preparation for gas chromatography (GC) analysis of the ethanol content. A solvent mixture of acetonitrile and iso-butanol precipitated dissolved organic residues and reduced water content in GC samples at least by 90%. Results showed that this method could be successfully used for bioethanol production from seaweed.